The Development of High School Physics Learning Module on Wave Subject - Zulherman Zulherman (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2018)
This research is aimed to develop high school physics teaching materials that can provide independent learning to high school students in Physics learning, in accordance with the demands of the curriculum. The research applied research development methods. It is implemented in FKIP Universitas Muhammadiyah Prof.DR.HAMKA and the trial and implementation are done in a number of high schools in Jakarta in 2017. The development of physics learning module with contextual approach was implemented in several stages, the first is analysis, the second is feasibility test, and the last is field trial. The instruments consisted of needs analysis questionnaire, validation sheet of feasibility test, and validation sheet of the test results. The module developed was validated by senior physics teachers in several high schools in Jakarta. The validation shows interpretation score of 73% - 93%. Physics learning module with contextual approach on wave material already has correct components, and it is feasible to be used as a companion module.